P124 Latent and active tuberculosis in patients with inflammatory bowel disease under anti-TNF—data from a centre with high incidence of tuberculosis. (25th January 2019) - Sousa, M; Ladeira, I; Fernandes, C; Ponte, A; Rodrigues, A; Silva, A P; Rodrigues, J; Silva, J; Gomes, C; Carvalho, J
Abstract: Background: Portugal is one of the countries with the highest tuberculosis burden in the European Union, with a reporting rate in the North region registered in 2016 of 21.6 cases per 100000 inhabitants. Anti-TNF can increase up to five times the reactivation of tuberculosis in patients with latent infection (LT). Therefore, it is recommended its diagnosis and treatment before starting biological therapies. Methods: A single-centre retrospective study in the North region of Portugal included patients with inflammatory bowel disease (IBD) who started anti-TNF treatment between 2013 and 2017. The aim was to evaluate the prevalence of LT before initiating anti-TNF and the percentage of active infection during treatment. Screening of LT was considered positive if the tuberculin test (TST) ≥ 5 mm in immunocompromised patients or TST ≥ 10 mm in immunocompetent patients, positive/indeterminate Interferon Gamma Release Test (IGRA) or history of contacts. Active infection was excluded using chest X-ray and clinical history. Results: One hundred and seventeen patients were identified—56% female, mean age 40 years, 91% Crohn's disease, 9% ulcerative colitis; 79% started infliximab, 21% adalimumab and 1% golimumab. The prevalence of LT was 32% ( n = 37)—TST positive in 18 patients (51%); IGRA positive in 14 patients (40%) and undetermined in 7 (6%); history of contacts in 11 patients (31%). During screening 61% of the patients were under immunosuppressive therapy. All patients screened with LT performed isoniazid for 9 months. During follow-up (mean 21.6 months), one patient under infliximab developed pleural tuberculosis 5 years after receiving treatment with isoniazid. None of the patients with negative LT screening had active tuberculosis. Conclusions: In this sample of patients with IBD, the occurrence of LT before starting biological treatment was significant (32%) but only 1 patient had active tuberculosis after TL treatment.